Ecological-economic evaluation of modern receptions of growing vegetable products - Gololobova О. О.; Kravchenko N. B.; Masovets Zh. V. (V. N. Karazin Kharkiv National University, 2017)
A modern study of the role of silicon in the physiology of cultivated plants, in the soil fertility and in the production of quality and environmentally safe plant products remains one of the pressing and in-demand in practice. Purpose. Assessment of environmental and economic efficiency of modern methods of growing vegetables. Methods. Field, atomic absorption spectrophotometry, variance. Results. Field studies have been conducted on the plot of land in the village of. Orihikka of the Lubny District of the Poltava region during 2015-2016. In the autumn of 2015, an experiment with the following plot variants was planted on the plots: 1. Control - a plot without fertilization; 2. control – +2 foliar feeding; 3. N60P40K60; 4. N60P40K60 + 2 foliar nutrition; 5. 30 t / ha semi-perforated manure; 6. 30 t / ha semi-permafrost + 2 extra root feedings. The area of each site was 15 m2. Repeat options - triple.For siliceous-potassium foliar nutrition, complex fertilizers containing silicon and potassium "Quantum-AQUASIL" were used. The agrostatus of our choice is the steel plate feeding of vegetable plants of tomatoes and sweet pepper, which is carried out by 0.5% solution of the preparation by standard spraying in the evening in the second, fourth and sixth variants of the experiment. Two treatments were carried out: the first-in-phase of budding, the second - at the beginning of the formation of fruits.Researched ahrostatus not cause soil contamination with heavy metals. The maximum increase of harvest tomatoes in the experiment is 13.2 kg / ha of sweet pepper in the experiment is 5.2 kg / ha on the background of manure and foliar nutrition siliciclastic-potassium fertilizer. The same results were obtained for the variant with the introduction of complete fertilizer and foliar nutrition siliciclastic-potassium fertilizer. Against the background of manure siliciclastic double-sheet feeding potash contributed detox effect with respect to heavy metals, pollutants and also helped to shape better trace element ...